Античний міф на берегах Дністра - Калініченко, Віталій; Ільків, Микола; Пивоваров, Сергій (Чернівці, Технодрук, 2019)
During the late nineteenth and mid-twentieth centuries in the village Vasyliv in Bukovyna recorded various variants of the legend of skilled masters, witch built monumental temple and made an unsuccessful attempt to escape on his own wings made. It is obvious that the legend was based on the famous Greek myth of Daedalus and Icarus. However, the people’s memory also retains real information about the existence of an ancient city on the banks of the Dniester with a mighty castle and monumental architecture, including a magnificent stone temple.
Ancient myth on the coast of the Dniester
Keywords: літописний Василів на Дністрі; легенди і перекази; міф про Дедала й Ікара; мікротопоніми